Preliminary Results from a Study to Estimate the Cost of Errors in a Firm's Aggregate Predictions - Merv Daub (Queen's University, Department of Economics, 1971)
Clearly there are many aggregate factors which affect all firms in the economy to some degree. Presumably there are others which differentially affect individual industries. Industry considerations aside, any particular firm would want to formulate 'own-firm' expectations incorporating aggregate expectations at least insofar as it felt aggregate events important. As regards the firm making the forecasts, the important standard of 'accuracy' might rather be economic consequences for its operations of these forecasts errors (which may or may not be adequately approximated by absolute error criteria).
Keywords: 330